2018
DOI: 10.1073/pnas.1803636115
|View full text |Cite
|
Sign up to set email alerts
|

Multiple prebiotic metals mediate translation

Abstract: SignificanceRibosomes are found in every living organism, where they are responsible for the translation of messenger RNA into protein. The ribosome’s centrality to cell function is underscored by its evolutionary conservation; the core structure has changed little since its inception ∼4 billion years ago when ecosystems were anoxic and metal-rich. The ribosome is a model system for the study of bioinorganic chemistry, owing to the many highly coordinated divalent metal cations that are essential to its functi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 66 publications
(84 reference statements)
2
55
0
Order By: Relevance
“…Experimentation with origins in hydrothermal vents [147][148][149] and geothermal fields [150][151][152] have taken into consideration geological insights in their OoL scenarios. In particular, the importance of relevant metals and metal clusters in the Hadean has settled in experimental work that recreates the origin of biochemistry in vitro, including carbon cycling [98,103,153], nitrogen fixation [154], ribosomal translation [155], and even the generation of pH gradients [156]. Simulated hydrothermal conditions, in particular pores, select for the replication of longer oligonucleotides [157].…”
Section: On the Right Track? Looking At The Past Decadementioning
confidence: 99%
“…Experimentation with origins in hydrothermal vents [147][148][149] and geothermal fields [150][151][152] have taken into consideration geological insights in their OoL scenarios. In particular, the importance of relevant metals and metal clusters in the Hadean has settled in experimental work that recreates the origin of biochemistry in vitro, including carbon cycling [98,103,153], nitrogen fixation [154], ribosomal translation [155], and even the generation of pH gradients [156]. Simulated hydrothermal conditions, in particular pores, select for the replication of longer oligonucleotides [157].…”
Section: On the Right Track? Looking At The Past Decadementioning
confidence: 99%
“…How other ions with different properties are able to promote RNA folding is not well understood (26). Ribosomal Mg 2+ can be substituted with other divalent cations, including Fe 2+ or Mn 2+ (27)(28)(29)(30) and the ribosome can competently mediate translation in this state (30).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has drawn on the interesting observation that while evolution has conserved the ribosomal core through billions of years, the earth environment has changed dramatically over this time, and with it the bioavailability of the metals on which the ribosome structure depends. Metal levels in the aqueous environment prior to abiogenesis included high concentrations of Fe 2+ (36), while Mg 2+ was less abundant than today (30,37). With the evolution of photosynthesis and the increase in molecular oxygen, much of the iron was lost from the aqueous environment through precipitation (38).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that Mg 2+ can replace Fe 2+ at neutral pH but not at low pH. Fe 2+ was also able to substitute for Mg 2+ in DNA polymerases, RNA polymerases, DNA ligases, and in protein translation …”
Section: Introductionmentioning
confidence: 99%